2018
DOI: 10.1016/j.athoracsur.2017.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Lymphocyte Ratio: Prognostic Impact in Heart Surgery. Early Outcomes and Late Survival

Abstract: Elevated NLR is associated with a higher incidence of adverse outcomes after cardiac surgery. It is a predictor of operative as well as late mortality. Further studies are warranted to determine whether prophylactic treatment with antiinflammatory agents can prevent such outcomes. It may be warranted to include the baseline NLR as another variable in risk stratification of patients about to undergo cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 23 publications
3
50
1
1
Order By: Relevance
“…Preoperative biomarkers have been associated with worse outcomes in patients undergoing cardiac surgery. In the last decade, the preoperative NLR was introduced to cardiac surgery as a strong independent risk factor for adverse events . The value of preoperative biomarkers as a risk factor for adverse outcomes for a wide range of CHD or SV physiology is minimal .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative biomarkers have been associated with worse outcomes in patients undergoing cardiac surgery. In the last decade, the preoperative NLR was introduced to cardiac surgery as a strong independent risk factor for adverse events . The value of preoperative biomarkers as a risk factor for adverse outcomes for a wide range of CHD or SV physiology is minimal .…”
Section: Discussionmentioning
confidence: 99%
“…Among several inflammatory biomarkers, the neutrophil‐lymphocyte ratio (NLR), defined as the ratio of absolute counts of neutrophils to lymphocytes, has emerged as a valid biomarker in the stratification and prognosis for adults with coronary artery disease undergoing coronary artery bypass grafting (CABG) and in patients undergoing valve surgery …”
Section: Introductionmentioning
confidence: 99%
“…In a study that evaluated long-term mortality, it was shown that increased NLR means increased short-term complications and increased long-term mortality. This study also recommended adding the NLR to the charts of risk scoring before cardiac surgery (13). A broadly based metaanalysis revealed that the increase of NLR after surgery may predict the risk of new-onset atrial fibrillation (14).…”
Section: Discussionmentioning
confidence: 99%
“…An elevated neutrophil/lymphocyte ratio is reportedly to be correlated with the incidence of SSI after posterior lumbar instrumentation surgery [18] and cardiac surgery [19], while the perioperative neutrophil-lymphocyte ratio is correlated with survival in patients undergoing colorectal cancer surgery [20] and higher mortality in patients with breast and kidney cancer [21]. In the present study, consistent with the lack of difference between survivors and non-survivors in the number of preoperative treatments involving neoadjuvant chemotherapy and radiation (Table 1), there were no difference between survivors and non-survivors in the neutrophil/lymphocyte ratio before the start of surgery or after the end of surgery (Table 2).…”
Section: Discussionmentioning
confidence: 99%